Roman fort at Duntocher - Camden, William (Britannia: or, a Chorographical Description of the Flourishing Kingdoms of England, Scotland, and Ireland, and the Islands Adjacent, Vol. 4, 1806)
Series of engravings depicting remains and reconstructions of the Roman fort at Duntocher, a village in West Dunbartonshire, Scotland. Included are a sketch and profile of the ground where the fort stood (figures A and B), as well as detail views of a stone building and bridge (figures C and D).
Keywords: Great Britain; Travel; Voyages and travels; Ruined buildings; Scotland; Britannia (Camden, William); Fortification, Roman